Development Of A Stem-Based E-Pocket Book As A Learning Media On Green Chemistry Materials At MAN 2 Jambi City - Navalia Wardani; Muhammad Naswir; Afrida Afrida (Mathematics Education Study Program, 2025)
e-pocket book, also known as a digital pocketbook, is a combination of a pocketbook and a digital book that is small in size and contains all the information needed by the reader. This e-pocket book is developed using a STEM (science, technology, engineering, and mathematics) approach. This research aims to determine the feasibility of the STEM-based e-pocket book according to subject matter experts and media experts, to assess the evaluation of chemistry subject teachers, and to understand the students' responses to the developed media. This research is a development study using the Lee & Owens development model. The research instruments used were interview sheets and questionnaires. The analysis techniques used are qualitative data analysis and quantitative data analysis. The results of the media expert validation were 4.46 and the material expert 4.54, indicating that the produced STEM-based e-pocket book is suitable for use. The results of the teacher assessments and student responses from the STEM-based e-pocket book on green chemistry were categorized as very good, with an average score of 4.54 and a student response percentage of 88.62%, thus it can be concluded that it can be used as a learning medium